Preliminary Investigation of Formulated Two in One Filter Aids Material as VOC Adsorbent - Masdiana, N.; Rashid, M.; Hajar, S.; NorRuwaida, J.; R.Ammar, M. (International Journal of Engineering and Technology, 2018)
Continuous adsorption of toluene gas onto newly formulated filter aids was studied in packed-bed column. Two different ratios of formulated filter aids prekotAC (prekotAC 5:95 and prekotAC 10:90) Â which is a mixture between pre-coating material of PreKotâ„¢ and activated carbon was experimentally adsorbed toluene gas (100 ppm) at constant temperature (25oC) and flow rate (0.55 lpm) onto two different amount of adsorbents (5 and 10 mg) and the experimental breakthrough curve was obtained. The results showed that, bu using 10 mg samples, prekotAC 10:90 had longer time (28 min) to reach equilibrium point compared to prekotAC 5:95 (22 min) and the amount of adsorbent used significantly affect the adsorption performance where adsorption performance was directly proportional to the amount of adsorbent used.Â